2021
DOI: 10.18203/2320-6012.ijrms20214425
|View full text |Cite
|
Sign up to set email alerts
|

Acute on chronic liver failure- etiology, clinical profile, prognostic scores: experience from tertiary care centre of eastern India

Abstract: Background: Acute on chronic liver failure (ACLF) is a recently recognised entity in chronic liver disease patients. Data regarding ACLF in terms of clinical presentation, etiology of underlying cirrhosis, precipitating factors, prognostic factors are lacking from eastern India. The present study was undertaken to evaluate the above factors along with the assessment of short-term mortality (4 weeks) in patients of ACLF.Methods: In this prospective observational study, 120 patients diagnosed as ACLF were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In contrast, Mikolasevic et al in 2015 [ 19 ] identified alcohol as the leading cause of CLD in 77.7% of their study population, while Garg et al in 2012 [ 18 ] and Tasneem et al in 2017 [ 7 ] reported HBV as the most prevalent etiology, with incidences of 37% and 25% respectively. Similarly, Saxena et al (2020) [ 13 ] and Behera et al (2021) [ 17 ] also documented that alcohol was the most common etiology of CLD, followed by HBV and HCV. Saad et al (2022) [ 15 ] reported a high prevalence of HCV at 78%, similar to the current study.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In contrast, Mikolasevic et al in 2015 [ 19 ] identified alcohol as the leading cause of CLD in 77.7% of their study population, while Garg et al in 2012 [ 18 ] and Tasneem et al in 2017 [ 7 ] reported HBV as the most prevalent etiology, with incidences of 37% and 25% respectively. Similarly, Saxena et al (2020) [ 13 ] and Behera et al (2021) [ 17 ] also documented that alcohol was the most common etiology of CLD, followed by HBV and HCV. Saad et al (2022) [ 15 ] reported a high prevalence of HCV at 78%, similar to the current study.…”
Section: Discussionmentioning
confidence: 97%
“…Saad et al (2022) [ 15 ] reported a higher mean age of 62 ± 7.2 years. Kulkarni et al (2018) [ 16 ] observed median ages of 42 years for those who survived and 47 years for those who did not (p=0.667) [ 16 , 17 ]. Tasneem et al (2017) [ 7 ] reported that individuals over 40 years exhibited a higher risk of mortality (p=0.036, Odds Ratio [OR] = 0.325).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations